The association between dietary sodium density and Hashimoto’s thyroiditis in US adults - An, Peilin; Wang, Silin; Liu, Lingyun; Li, Xuelin; Lv, Xin (Frontiers in Nutrition, 2025)
BackgroundHashimoto’s thyroiditis (HT) is an autoimmune thyroid disease characterized by the presence of antibodies against thyroid-specific antigens. Dietary sodium intake has been implicated in the development of several autoimmune diseases, but its association with HT remains unclear.MethodsThis study investigates the relationship between dietary sodium density (the ratio of sodium to energy intake) and HT using data from the National Health and Nutrition Examination Survey (NHANES) from 2007 to 2012. A cross-sectional study was conducted using NHANES data, focusing on adults aged 20 years and older with available dietary and thyroid profile data. Sodium density was calculated from two 24-h dietary recall interviews. Logistic regression models were used to evaluate the associations of sodium density with HT, thyroid peroxidase antibody (TPOAb) and thyroglobulin antibody (TgAb). Restricted cubic spline (RCS) analyses were performed to explore non-linear relationships.ResultsA total of 6,258 participants were included, with 576 (9.20%) diagnosed with HT. An additional unit of dietary sodium density was associated with a 24% increased risk of HT (OR 1.24, 95% CI 1.01–1.50) in adjusted model. A breakpoint at 2.43 mg/kcal in dietary sodium density was identified using a piecewise regression model. Below this threshold, HT risk increased with rising sodium density, while above it, the risk plateaued. Higher sodium density was also associated with increased TPOAb positivity (OR 1.28, 95% CI 1.05–1.56), but not TgAb positivity.ConclusionElevated dietary sodium density is associated with an increased risk of HT and TPOAb positivity, suggesting that sodium intake may play a role in the pathogenesis of HT.